Effectiveness of an Instructional Program on Patientsꞌ Knowledge about Home Safety While Receiving Anti -Cancer Medications at Al- Karama Teaching Hospital in Al-Kut City - Jassim Mohammed Abid,; Widad K. Mohammed, (Iraqi National Journal of Nursing Specialties, 2022)
Objectives: To determine the effectiveness of the instructional program on patients’ knowledge about home safety while receiving anti-cancer treatment at  Al- Karama Teaching Hospital in Al-Kut City.Methodology:   A quasi-experimental design is conducted through the application of a pre-test and post-test approach for the study and control groups from February 5th, 2020 to April 25th, 2020. A non–probability (purposive) sample of (50) patients treated at the Blood Disease and Oncology Center is selected and divided into two groups. Each group contains (25) patients as control and study groups. An instrument is constructed that is comprised of two parts; the first part consists of demographic data for a study sample which is consisted of (5) items of age, gender, occupation education and marital status. The second part is multiple choice questions related to patients’ knowledge which is consisted of (20) items. Validity and reliability of the instrument are determined through pilot study.Results:  The findings of the study show that the evaluation of patients’ knowledge in the study groups throughout three periods of measurements showed that most of the studied items had a low means of score (1.23) before applying the instructional program. Comparatively, most of the studied items had a high mean of score (1.77 and 1.70) in post-test I and post-test II after implementation of the program. Furthermore, the evaluation of patients’ knowledge in the control group throughout two periods of measurement shows very slight change in the mean (1.26) to the mean (1.3). Recommendations: The study recommends that encouragement of continuous nursing education units to meet with patients under the care of Oncology Physicians to teach them about home safety during chemotherapy treatment and the hospital should establish regular training sessions, lectures, workshops, and programs to improve patients’ knowledge about home safety during treatment.